STRATEGI INDUSTRI MANUFAKTUR DALAM MENINGKATKAN PERCEPATAN PERTUMBUHAN EKONOMI DI INDONESIA - Ravellino Dwi Cahya; Muhammad Yasin (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
Indonesia is a developing country and the economic development activities carried out aim to reduce existing economic problems. This is done through industrialization. Manufacturing Industry almost always gets the main priority in a developing country's development plans. Important challenges facing the Indonesian manufacturing industry sector include the possibility of disparities in the level of efficiency and productivity of each sub-sector of the Indonesian manufacturing industry.  Industrialization is one thing that can encourage GRDP and economic development. However, industrialization carried out in several regions has not been able to provide high, stable and sustainable economic growth as well as high economic resilience against various threats. The aim of this research is to find out more effective industrialization strategies in the economic structure in Indonesia. This research uses qualitative methods with a library research approach. The results of this research are that the manufacturing industry strategy in increasing the acceleration of Indonesia's economic growth is carried out by implementing industrial strategy 4.0. With support in the form of a systematic and well-integrated Industry 4.0 development platform for a unified ecosystem, it is hoped that collaboration can be created between stakeholders so that joint technical standards/platforms can be developed so that a domestic market that is competitive and independent can be created.